Terapi Meditasi Mindfulness Terhadap Insomnia di Asrama Polisi Diklat Reserse Megamendung Kabupaten Bogor - Okeu Kurniawan, Muhamad; Gunardi, Saiful (An-Najat, 2025)
Abstract. Introduction: Every individual is required to always meet basic needs in order to maintain survival. One of the basic needs that humans need is sleep. One of the sleep disorders that is often experienced is insomnia, namely the inability of a person to sleep with sufficient amount and quality. Meditation techniquemindfulness is one of the techniques used to improve the quality of sleep in the general public who experience problems with poor sleep quality.Objective: To Know the effectiveness of meditation therapy exercises mindfulness against people who experience insomnia in the Megamendung Investigation Police Training Dormitory, Bogor Regency. Method:This study uses a quantitative research type, with a research design quasy-experimental, with the research design model ispre-test and post-test control group design. With statistical analysis used is Independent Sample T-test to compare the differences between the intervention group and the control group. Results: From the results of the independent sample t test, the P value between the intervention group and the group is 0.000 or <0.05 which indicates a difference between the control group and the intervention group. Conclusion: The results of this study indicate that mindfulness meditation therapy is effective in reducing insomnia levels in the Megamendung Police Research and Training Dormitory, Bogor Regency.